Measuring customer satisfaction on service quality in Bank Rakyat / Raja Harun Tengku Wasimah - Raja Harun, Tengku Wasimah (Faculty of Business and Management, 2011)
The purpose of this research is to study the customer satisfaction towards the service quality at Bank Rakyat Cawangan Machang located in Kelantan. This research will used questionnaires as a primary data collection instead of using secondary data such as journals, articles, thesis report and etc. One hundred (100) of Bank Rakyat Machang’s customers will be involved as a respondent for this research. This research will be implemented by using SERVQUAL models that contained five dimensions which are tangible dimension, empathy dimension, responsiveness dimension, reliability dimension and assurance dimension. The purposive as well as judgement sampling technique will be used in order to collect the data for this study. Due to the technology advancement that has led to an integrated banking industry, this contributes to the highly competitive marketplace. In this situation, the bank management should identify and improve upon matters that can meet with the customers’ satisfaction. This will include the employee performance, willingness to solve the problem that faced by the customers, friendliness, level of knowledge towards the business and etc. In order to secure the bank’s long-term interest, the organization that provide services will seek ways to forge and to maintain an on-going relationship with the customers in order to ensure the customers’ loyalty with the organization (Kandampully, 1998). Therefore, the measurement of service quality at Bank Rakyat Cawangan Machang is important in order to improve their services and help them deliver the best services to the customers.